The function of irony in the composition of a neo-romantic short story - Irina Klimenko (Vestnik Pravoslavnogo Svi͡a︡to-Tikhonovskogo gumanitarnogo universiteta. 3, Filologii͡a, 2024)
This article raises the issue of ironic effects manifestation at the composition level. The novelistic part of the work of the neo-romanticist A. Grin was chosen as the research material, the ironic mode in whose artistic method has not previously been subjected to detailed analysis. The relationship between irony in neoromanticism and classical romantic irony is considered. In romanticism, irony indicates an understanding of the incompleteness of knowledge about the world as a whole, the distancing of the narrating subject (be it the artist himself, the image of the author or the narrator) from the object of the narration; moreover, “double reflection” arises, since the romantics, through estrangement, distance themselves from their own work, creating parodies and auto-parodies of it. The features of romantic poetics thus identified later turn out to be objects of rethinking and parody in other literary movements, including neoromanticism. For example, the “irony of fate” discovered by the romantics is manifested in the composition of A. Grin’s stylistically non-ironic stories and successfully combined with the features of the compositional structure of novella , in which the obligatory plot twist can illustrate the tragic discrepancy between life expectations and reality. Moreover, cliches formed in romantic and post-romantic literature are artistically interpreted at the plot and stylistic levels. This kind of an appeal to the reader’s experience, dialogicity, and allusiveness become the basis for the Green’s stories composition. Duality can also be created when irony in composition is supported by stylistic irony. For example, in “The Headless Horseman (18th Century Manuscript)”, which refers to “The Legend of Sleepy Hollow” by W. Irving, the comic naivety of the character is emphasized both by mocking the romantic cliches, that form the basis of the narrative style, and by constructing the composition in such a way that the reader imagines the outcome of the described events more clearly than the character himself. The ironic mode manifests itself in the interaction with the implicit reader, who turns out to be an emphatically necessary participant. It creates two points of view, which relationship strengthens the compositional unity.